Digital Transformation Strategies for Operational Resilience in Manufacturing: A Case Study Approach - Ade Bani Riyan (Politeknik Siber Cerdika Internasional, 2024)
This study examines the impact of digital transformation strategies on operational resilience within the manufacturing sector through a qualitative case study approach. Data were collected from five manufacturing firms across the automotive, electronics, and consumer goods sectors, focusing on the role of technologies such as IoT, data analytics, and automation in enhancing agility and responsiveness. Findings indicate that digital transformation initiatives, particularly IoT and predictive analytics, significantly improve operational resilience by enabling real-time data collection, proactive risk management, and enhanced decision-making. However, challenges such as employee resistance and integration with legacy systems highlight the need for tailored implementation strategies, including phased technology adoption and comprehensive training programs. This study supports theories of dynamic capabilities and resilience, suggesting that a strategic alignment of digital transformation efforts can foster long-term operational adaptability. Practical implications emphasize the importance of embedding digital initiatives within overall organizational strategy to ensure resilience in dynamic market conditions. Future research could explore the long-term impacts of digital transformation on resilience across various sectors.